Qualitative Study on Informal Payments for Health Services in Georgia - Belli, Paolo; Shahriari, Helen; Curtio Medical Group (World Bank, Washington, DC, 2013)
This paper focuses on the specific dimension of informal payments by health users in Georgia, a growing pattern within many ECA (East Europe and Central Asia) countries. Using newly collected data from in-depth interviews and focus groups in rural and urban areas of the country, it investigates the determinants of out-of-pocket payments for health services that are supposed to be delivered free of charge under the Georgian Basic Benefit Package (BBP). The study finds that the demarcation between formal and informal components of these Out-of-Pocket payments is extremely imprecise because of: (a) the spread of "health rights unawareness" around the country and, (b) the prices outside the BBP differ from provider to provider. The study also found that some informal payments are based on cultural/social patterns ingrained in the Georgian tradition. Georgian now about the low health sector salaries and compensate the doctors with small payments. Finally, some recommendations to help the Georgian government to break the vicious cycle (excess capacity, decreasing demand of health services, lack of accountability) are proposed in this study, including greater role of the government in leading reforms, and the wider participation of the private sector in designing new governance arrangements in the future.